The crucial and unique role of extreme tropical cyclones in promoting freshwater invasions in China - Shimin Gu; Dangen Gu; Lu Shu; Zhiqiang Lin; Weishan Tu; Yuchen Wang; Xuan Liu (Proceedings of the National Academy of Sciences, 2026)
Climate change induced extreme weather events (EWEs) and invasive species are major threats to global biodiversity and social economy; however, the unique role of EWEs in facilitating biological invasions remains uncertain. Here, we compiled an extensive dataset of landfalling tropical cyclones (TCs) over the past 70 y covering thousands of kilometers of the Southeast China coast. Through intensive field surveys and environmental DNA investigations, we found that the richness and relative abundance of nonnative freshwater animals, especially fishes, were greater at TC-frequent sites than at TC-free sites after accounting for effects of water body landscapes, native biodiversity, and anthropogenic factors such as aquaculture and religious release of nonnative animals. Nevertheless, no significant differences were observed in native species richness or relative abundance between TC-frequent and TC-free sites. TC-induced precipitation, wind, and natural discharge were the key hydrometeorological parameters for predicting invasions. Our findings highlight the importance of developing proactive strategies against the combined impacts of EWEs and biological invasions under sustained global change.